Tracing the Footsteps of Muslim Scientists: The Integration of Religion and Science in Classical Islam - Amaliyah, Nur; Musawamah, Aprilia; Saad, Suadi; Anwar, Endang Saeful (ALSYS, 2025)
The development of science in classical Islam reflects a profound integration of religious and empirical knowledge, forming a foundational pillar of the intellectual and societal achievements of Islamic civilization. In contrast, contemporary scientific paradigms often maintain a strict separation between these domains, contributing to persistent challenges in education, research, and public policy. This study aims to examine the integrative patterns of science within the classical Islamic tradition and evaluate their relevance to contemporary contexts. Adopting a qualitative methodology, the research applies a historical and descriptive-comparative approach to analyze seminal works of classical Muslim scholars and their enduring influence on modern scientific thought. Data were drawn from an extensive array of primary sources, such as classical texts, and secondary sources, including academic journals and recent studies on science integration. The findings reveal that the classical Islamic model marked by a balanced synthesis of rational inquiry and spiritual values retains significant applicability in shaping modern educational frameworks, research ethics, policy formulation, and global scientific engagement. The study concludes that revitalizing this integrative epistemological approach can address current scientific and societal challenges by promoting holistic education, ethically guided research, and policies that align scientific advancement with humanistic and moral values.